Comprehensive and Rapid Real-Time PCR Analysis of 21 Foodborne Outbreaks - Hiroshi Fukushima; Kazunori Katsube; Yoshie Tsunomori; Ryoko Kishi; Junko Atsuta; Yuko Akiba (International Journal of Microbiology)
A set of four duplex SYBR Green I PCR (SG-PCR) assay combined with DNA extraction using QIAamp DNA Stool Mini kit was evaluated for the detection of foodborne bacteria from 21 foodborne outbreaks. The causative pathogens were detected in almost all cases in 2 hours or less. The first run was for the detection of 8 main foodborne pathogens in 5 stool specimens within 2 hours and the second run was for the detection of other unusual suspect pathogens within a further 45 minutes. After 2 to 4 days, the causative agents were isolated and identified. The results proved that for comprehensive and rapid molecular diagnosis in foodborne outbreaks, Duplex SG-PCR assay is not only very useful, but is also economically viable for one-step differentiation of causative pathogens in fecal specimens obtained from symptomatic patients. This then allows for effective diagnosis and management of foodborne outbreaks.